“That’s the dream, right?”: reflections on the co-design of an environmental digital twin by flood risk management professionals - Underhill, Helen; McEwen, Lindsey; Coulthard, Thomas (Frontiers in Environmental Science, 2026)
A Digital Twin (DT) dynamically represents the near-real-time status of a system, allowing users to visualise its current and forecasted status, and test interventions. Emerging technologies, such as DTs, could be transformative for working practices in environmental risk management. However, the development of DTs for environmental management and disaster risk reduction involves extensive challenges. Within Flood Risk Management (FRM), this process is complicated by the involvement of multiple professional stakeholders with diverse statutory responsibilities, priorities, and needs. There is also no formal method for the design of DTs or established method of accounting for end user needs. Processes tend to be top-down and technology driven, rather than bottom-up and user focused. This paper presents one of the first attempts to explore user co-design within the development of a DT. It stems from FLOODTWIN - an interdisciplinary DT demonstrator project for FRM in Hull and the East Riding of Yorkshire (United Kingdom), a region with complex, compound flood risk. Using data from participatory workshops and interviews, we explore the project’s co-creation process with professional FRM stakeholders, mapping emerging opportunities and challenges in the development of DTs and their interfaces from a qualitative, ethnographic perspective. We reflect on the diverse perspectives of professional users, how they engage with emerging technologies, the politics of data-sharing, and the role of academic research in shaping future development of DTs in FRM practice. We present a new evidence-base to inform future research on the co-creation of digital tools in multi-agency decision-making for FRM and wider environmental management. The paper proposes a research planning framework for navigating co-design processes in future projects to develop environmental DTs. In so doing, the paper also illustrates ways in which sub-optimal water risk management is socially constructed, and not merely a technical challenge to be surmounted.